Reduction in upper limb joint surgery among rheumatoid arthritis patients: An interrupted time-series analysis using Danish health care registers - Cordtz, R; Hawley, S; Prieto-Alhambra, D; Højgaard, P; Zobbe, K; Kristensen, LE; Overgaard, S; Odgaard, A; Soussi, BG; Dreyer, L (Wiley, 2020)
Objectives Joint replacement surgery is a proxy of severe joint damage in rheumatoid arthritis (RA). The aim of this study was to assess the impact of the introduction of biologic disease‐modifying antirheumatic drugs (bDMARDs) on the incidence rate (IR) of upper limb joint replacements among newly diagnosed RA patients. Methods Using the Danish National Patient Register, patients with incident RA from 1996–2012 were identified. Each patient was matched on age, sex, and municipality, with up to 10 general population controls. The age‐ and sex‐standardized 5‐year IR per 1,000 person‐years of a composite outcome of any first joint replacement of the finger, wrist, elbow, or shoulder was calculated, and an interrupted time‐series analysis was undertaken to investigate trends and changes of the IR in the pre‐bDMARD (1996–2001) and the bDMARD eras (2003–2012), with a 1‐year lag period in 2002. Results In total, 18,654 incident patients with RA were identified (mean age 57.6 years, 70.5% women). The IR of joint replacements among patients with RA was stable at 2.46 per 1,000 person‐years (95% confidence interval [95% CI] 1.96, 2.96) from 1996 to 2001 but started to decrease from 2003 onwards (–0.08 per 1,000 person‐years annually [95% CI –0.20, 0.02]). Compared with patients with RA, the IR among controls in 1996 was 1/17 and increased continuously throughout the study period. Conclusion The IR of upper limb joint replacements started to decrease among patients with RA from 2002 onwards, whereas it increased among controls. Our results suggest an association between the introduction of bDMARDs and a lower need of joint replacements among patients with RA.